Excise Tax Increases and the Rise of Illicit Cigarettes in Bali Province - Fachri Arsyadani; Nyoman Sri Subawa (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study examines how well Indonesia’s excise tax policy reduces cigarette consumption in Bali Province, focusing on illicit cigarette circulation as a middle factor and economic, psychological, and law enforcement elements as adjusting factors. The aim is to check direct effects of tax increases on consumption, the mediating role of illicit circulation, and moderating influences, while suggesting better policy coordination. A quantitative approach uses partial least squares structural equation modeling on data from 358 adult smokers across nine districts, collected through an online questionnaire with five-point agreement scales. Results show tax rises strongly boost illicit circulation but only slightly raise total consumption, with no significant mediation as illegal products simply replace legal ones. Law enforcement weakens the tax-illicit link, but economic and psychological factors do not. In conclusion, excise hikes alone fail to curb smoking due to low price sensitivity and substitution; integrated fiscal-enforcement measures, regional rate adjustments, digital tracking, and public education are needed for effective health and revenue outcomes.